Carbon nanoparticles fabricated by infrared laser ablation of graphite and polycrystalline diamond targets. Issue 2 (17th October 2016) - Dudek, Mariusz; Rosowski, Adam; Koperkiewicz, Anna; Grobelny, Jaroslaw; Wach, Radoslaw; Sharp, Martin; French, Paul; Janasz, Lukasz; Kozanecki, Marcin
Abstract : This paper presents the results of carbon nanoparticles (CNPs) production by infrared laser ablation of a graphite or a polycrystalline diamond target, submerged in one of two solvents, water or isopropanol. The targets were irradiated using a SPI fibre laser with a wavelength of 1064 nm being operated at different average powers. After laser‐assisted synthesis of CNPs, the resulting colloids, i.e particles in a liquid medium, were examined using the analytical techniques of dynamic light scattering, UV‐Vis, Raman spectroscopy and fluorescence spectroscopy. The results show that the properties of CNPs strongly depend on processing conditions of the liquid phase‐pulsed laser ablation (LP‐PLA) process. In particular, the size of nanoparticles produced are affected by the processing parameters of the laser ablation. The results show that the laser processing of a graphite target in deionised water and in isopropanol produces carbon nanoparticles with properties that are beneficial for various biochemical and biomedical applications.